Efek Ekstrak Jintan Hitam (Nigella sativa L.) terhadap Gambaran Histopatologi Hepar Tikus Putih (Rattus norvegicus) yang Diinduksi Isoniazid - Kartika Sari; Rizki Muharani; Syalfinaf Manaf; Hilda Taurina; Liya Agustin Umar; Novriantika Lestari (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aimed to examine the effect of giving black cumin extract to changes in the histopathological picture of the liver of white rats induced by isoniazid. The method used is experimental with posttest only control group design pattern. The research subjects used 25 Rattus norvegicus, which were divided into negative control group (P1), positive control (P2) isoniazid orally with a dose of 5.4 - 6.75 mg/day for six weeks, treatment 1 (P3), treatment 2 (P4 ), and treatment 3 (P5) which was given isoniazid at a dose of 5.4 - 6.75 mg/day orally and followed by oral black cumin with stratified amounts of 2000, 2500 and 3000 mg/kgBW. The results showed that there was a significant increase in liver cell damage after administration of isoniazid (p < 0.05) and liver cell recovery after administration of black cumin extract for 42 days (p < 0.05). In conclusion, the administration of black cumin extract can restore isoniazid-induced liver cell damage. Keywords: Liver Histopathology, Isoniazid, Black Cumin